1992
DOI: 10.1063/1.463594
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of freezing in a confined geometry

Abstract: The dynamics offreezing of a Lennard-Jones liquid in narrow channels bounded by molecular walls is studied by computer simulation. We quantify the time development of ordering and observe a novel freezing mechanism. The liquid forms layers and subsequent in-plane ordering within a layer is accompanied by a sharpening of the layer in the transverse direction. The effects of channel size, the methods of quench, the liquid-wall interaction and the roughness of walls on the freezing mechanism are elucidated. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 41 publications
(4 reference statements)
1
19
0
Order By: Relevance
“…This structure was first considered [20] in conjunction with the structure of Cobalt and observed in systems of hard colloid spheres [21]. Molecular dynamics simulations of Lennard-Jones liquids solidifying in narrow channels bounded by molecular walls observed a solid with a hexagonal lattice within each layer [22]. However, no periodicity was observed in the stacking of the layers, reminiscent of the dhcp structure that we have assigned to the confined rare gas solids.…”
mentioning
confidence: 87%
“…This structure was first considered [20] in conjunction with the structure of Cobalt and observed in systems of hard colloid spheres [21]. Molecular dynamics simulations of Lennard-Jones liquids solidifying in narrow channels bounded by molecular walls observed a solid with a hexagonal lattice within each layer [22]. However, no periodicity was observed in the stacking of the layers, reminiscent of the dhcp structure that we have assigned to the confined rare gas solids.…”
mentioning
confidence: 87%
“…A complete study of the influence of the Ar-wall interaction parameters and of the nature of the pore itself (structureless, crystalline or amorphous) is certainly necessary for a complete ''microscopic understanding'' of the behaviour of the geometry of (mesoscopic) porous systems on adsorption, capillary condensation and freezing transitions can be found in the literature (see for instance [11][12][13][14]). In this work, the pore in which the cluster is confined is structureless.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Therefore, it is suggested that the solid invasion will be stopped at the throat' 2 ( the smallest pore size of the media). Based on the neutron scattering investigation of liquid 02 and D 2 in porous vycol glass by Sokol et al 4 and the computer simulation by Ma et al 6 , on the other hand, the results suggest that the fluids inside the pores freeze layer by layer initiating from the wall. The results for the TNT confined 20 nm pores with bulk on the outer surface strongly suggests that the freezing of the bulk TNT indeed can trigger the freezing transition of the confined TNT inside the pores because at the bulk freezing temperature Tbf , all the confined TNT molecules are in the supercooled state, i.e., Tbf < T,.…”
Section: Tnt Physically Confined In 10 and 20 Nm Pores With Bulk On Omentioning
confidence: 99%
“…In the case of freezing and melting transitions, three assumptions must be made with this model: 1) The substrate wall is more favorable a liquid-wall interface than a solid-wall interface, 2) nucleation occurs at the pore center, and 3) nucleation process is restricted in the reduced dimension. A computer simulation study 6 of molecular freezing dynamics of a Lennard-Jones liquid in a confined geometry has predicted the time development of ordering and a novel freezing mechanism. Upon cooling, the confined liquid forms layers near the pore wall and a subsequent in-plane ordering within a layer is accomplished by a sharpening of the layering in the transverse direction, which is also qualitatively supported by neutron scattering experiments of Sokol et al 4 On the other hand, the simulation can not provide information on supercooling effects for confined fluids.…”
Section: Introductionmentioning
confidence: 99%